PANDUAN DWIBAHASA PRANIKAH (DIGITAL) PERSPEKTIF MAQOSHID SYARIAH : STRATEGI PREVENTIF PERCERAIAN KELUARGA DI KABUPATEN BOJONEGORO - Nilna Indriana; Agus Sholahudin Shidiq; Ida Fauziatun Nisa (FASTABIQ: JURNAL STUDI ISLAM, 2026)
A total of 2,360 divorce cases were recorded in Bojonegoro Regency as of October 2024. The number of divorce cases in this regency has consistently exceeded 2,000 cases each year. In 2023, there were 2,823 cases; in 2022, 2,950 cases; and in 2021, 2,690 cases. The divorce rate in Bojonegoro Regency is 4.5 times higher than that of the neighboring Tuban Regency, which recorded only 1,668 cases in 2023. This situation represents a serious issue requiring strategic intervention. This study aims to develop a bilingual premarital handbook based on the Maqashid Syariah perspective as a preventive effort to reduce divorce cases in Bojonegoro Regency. This is a strategic effort that can be done by compiling a Bilingual Premarital Guide (Digital) in Indonesian and Arabic which contains guidance on rights and obligations in marriage, politeness in household language and premarital guidance in Maqashid Syariah The use of a bilingual handbook is important as it provides easier access to information for diverse groups within society. Considering the varying educational backgrounds of the community, presenting the content in two languages is expected to expand the reach and accessibility of the information provided. The product is developed through Research & Development (R&D) using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. This study employs both qualitative and quantitative data collected through questionnaires and interviews. Research participants include three linguists, three marriage consultants, eleven counselors, and 120 future brides and grooms. Data analysis was conducted in three stages: condensation, data presentation, and conclusion drawing. The research results are a digital bilingual premarital guidebook based on the maqashid sharia perspective that has undergone expert and field testing. The feasibility levels obtained include material feasibility of 95.3%, design feasibility of 90.3%, readability of 91.7%, and practicality of 93.1%. Thus, it is declared feasible for implementation. In addition to serving as a divorce prevention measure in Bojonegoro Regency, this digital bilingual premarital guidebook can also be used as a supplement to marriage guidance activities (Bimwin) organized by the local KUA.